Pengaruh Intensitas Penggunaan Media Tiktok Terhadap Karakter Tanggung Jawab Siswa MI Ma’arif Bareng Tahun Pelajaran 2023/2024 - Susanti, Susi; Muqorrobin, Syamsul; Fuad Fitriawan (PGMI Fakultas Tarbiyah Universitas Islam Jember, 2024)
This social media is widely used by various groups, from children to adults. TikTok social media displays more interesting images, videos, audio and other features. Automatically they will search on social media, which is more interesting and fun, not boring content that makes their eyes dizzy and they forget to study, so they are lazy about doing activities that have a negative impact on themselves.This research examines whether there is an influence of the intensity of use of social media TikTok on the development of the responsible character of MI Ma'arif Bareng students? This research was conducted using quantitative methods at MI Ma'arif Bareng, Babadan, Ponorogo, with data collection procedures through observation, interviews and questionnaires. The collected data was analyzed correlationally using simple linear regression analysis. Based on data analysis, the results showed that (1) the intensity of use of social media TikTok among MI Ma'arif Bareng students is in the high category, because the frequency used is mostly more than 30 minutes every day, (2) the character of responsibility of MI Ma'arif Bareng students in the analysis results are quite low, because the character of responsibility is a very important issue, (3) there is an influence of 20.7%, the intensity of TikTok media influences the character of responsibility of students at MI Ma'arif Bareng, Babadan, Ponorogo.